If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2b + -7(5 + 4b) = 15 + -1b 2b + (5 * -7 + 4b * -7) = 15 + -1b 2b + (-35 + -28b) = 15 + -1b Reorder the terms: -35 + 2b + -28b = 15 + -1b Combine like terms: 2b + -28b = -26b -35 + -26b = 15 + -1b Solving -35 + -26b = 15 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. -35 + -26b + b = 15 + -1b + b Combine like terms: -26b + b = -25b -35 + -25b = 15 + -1b + b Combine like terms: -1b + b = 0 -35 + -25b = 15 + 0 -35 + -25b = 15 Add '35' to each side of the equation. -35 + 35 + -25b = 15 + 35 Combine like terms: -35 + 35 = 0 0 + -25b = 15 + 35 -25b = 15 + 35 Combine like terms: 15 + 35 = 50 -25b = 50 Divide each side by '-25'. b = -2 Simplifying b = -2
| 16=-2x-20 | | 20x+80y=13 | | 7(-1-b)=-8b-12 | | 12p+3-9p=12-6p | | 6x-(12-x)=10(x+6)-7 | | -5-15m+1=14m-32-m | | 3b-3-12b-4= | | -58+23=-8x+15x | | 5+8b=3b+5(5b+5) | | (2x-6)5+2((3-2x)3+(7x-18))=8+3 | | 2m+18=16-4m-28 | | -5.4=1.3+x | | -10+2x=14 | | 1.50b^2-24b-24=0 | | 6(2p-6)=7p+4 | | 4y(y-7)=2y-38 | | 6x-4-3x=-2x+7-1 | | 2n-25=-3(-5n+4) | | (x^2)-6x=24 | | s/5=42 | | 3x=2x+1.5 | | 2d+3s=21 | | 8y*48=-22 | | 3m=m-2 | | 7p-2=2p+3p+12 | | (200x^2)-9000x+99072=0 | | 5-(n-4)=3(n++2) | | 8x+4x=4x-16 | | n+1-1-15=3n-1 | | p-1+6=5-3p | | 86-(21x-(17x+25))=16x-449 | | 14=2y-10 |